Hysteresis Behavior and Design of the New Autoclaved Lightweight Concrete (ALC) External Panel Connector with the Steel Frame - Kewei Ding; Chikun Zhang; Shulin He; Yunlin Liu (Advances in Materials Science and Engineering)
This paper proposes a new flexible connector for the autoclaved lightweight concrete (ALC) panel with the steel beam. It is a universal upper and lower crossing connector, with load-bearing and limitation holes; then, the seismic capacity of this connector is investigated in the simulations and full-scale tests. Firstly, the finite element simulations of the new connector and traditional connector (L-hooked bolt) were made by ABAQUS, which proved the reliability of the new connector by comparing them in low-cyclic loading. Secondly, in order to analyze the phenomenon and data of the two connectors which are in the same test conditions of simulation, the full-scale tests of the steel frame were conducted. The damage of the ALC panel at different connectors and at different test load displacements is described in detail. The contribution of the connectors to the steel frame and the ALC panel is investigated in depth during the elastic, elastoplastic, and plastic stages of the steel frames. The test result is similar to the simulation result roughly, in which the new connector has better seismic capability. In minor earthquakes, the ALC panel frame with the new connector has better synergistic capacity of panels, while in large earthquakes, it can provide certain stiffness to the structure. Compared with the L-hooked bolt, the maximum bearing capacity of the structure with the new connector increases by 5.2%, and the yield displacement delays by 27.5%, which results in the increase of ductility by 9.8%. In terms of energy consumption capacity, the equivalent damping factor of the new connector increases by 10.2% and 35.3% at the yield and ultimate state, respectively. The FEM simulation results can represent the actual test results well. To summarize, the new ALC panel connector in this paper has excellent seismic capacity and good synergistic, which can provide a reference for the development and application of new types of the ALC connector.